2016
DOI: 10.1007/s00213-016-4341-7
|View full text |Cite
|
Sign up to set email alerts
|

The tendency to sign-track predicts cue-induced reinstatement during nicotine self-administration, and is enhanced by nicotine but not ethanol

Abstract: Rationale Some individuals are particularly responsive to reward-associated stimuli (“cues”), including the effects of these cues on craving and relapse to drug-seeking behavior. In the cases of nicotine and alcohol, cues may acquire these abilities via the incentive-enhancing properties of the drug. Objectives To determine the interaction between cue-responsivity and nicotine reinforcement, we studied the patterns of nicotine self-administration in rats categorized based on their tendency to approach a food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 72 publications
1
52
1
Order By: Relevance
“…Our model produced sign- and goal-tracking behavior similar to previous reports (Flagel et al, 2009; Palmatier et al, 2013b; Versaggi et al, 2016), as control animals exhibited individual preferences for the sign- or goal-tracking behavior. In addition, nicotine exposure increased the likelihood that an animal would display a sign-tracking response in Experiments 1 and 2.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our model produced sign- and goal-tracking behavior similar to previous reports (Flagel et al, 2009; Palmatier et al, 2013b; Versaggi et al, 2016), as control animals exhibited individual preferences for the sign- or goal-tracking behavior. In addition, nicotine exposure increased the likelihood that an animal would display a sign-tracking response in Experiments 1 and 2.…”
Section: Discussionsupporting
confidence: 82%
“…Sign tracking has recently come under increasing scrutiny in substance dependence research because of its association with drug abuse vulnerability (Saunders and Robinson, 2013; Tomie et al, 2008). Although both sign and goal tracking rely on the same mesotelencephalic systems implicated in substance dependence (Flagel et al, 2011b; Saunders and Robinson, 2012), individual subjects who display a greater propensity to sign track show increased drug self-administration (Saunders and Robinson, 2011; Versaggi et al, 2016). These individual differences are also linked to variation in stress responses, neurotransmitter release, and neuronal activation in areas including the PFC and the nucleus accumbens (Saunders and Robinson, 2013; Tomie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This task assesses sensitivity to cues in the environment, by measuring the ability of those cues to elicit approach behavior (Meyer et al , 2012a, Robinson et al , 2014). Response to Pavlovian reward cues have been further associated with response to drug-cues (Saunders & Robinson, 2010, Versaggi et al , 2016) and action impulsivity (King et al , 2016, Lovic et al , 2011). Response to environmental cues may explain one mechanism by which drug-associated stimuli come to prompt maladaptive behavior or drug seeking (Childress et al , 2008, Franklin et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that tendency to sign-track a food cue is associated with different patterns of drug-related behavior, including higher progressive ratio break-points during cocaine self-administration, more robust cocaine and nicotine cue-induced reinstatement, and stronger cocaine conditioned place preference (Meyer et al 2012b; Saunders and Robinson 2010; 2011; Versaggi et al 2016; Yager and Robinson 2013). For this reason, sign-tracking is considered a model for drug-cue responsivity, in that individuals displaying this behavior may be more vulnerable to the effects of cues on relapse to drug-taking (Flagel et al 2009; Saunders and Robinson 2013).…”
Section: Introductionmentioning
confidence: 99%